The Effect of Perceived Ads Personalization Toward Online Impulse Buying Tendency with Mediating and Moderating Variables, Evidence from Indonesian Millennial E-Commerce Customers - Joshua Christian; Febby Karissa; Boas Handoyo; Ferdi Antonio (KINERJA, 2021)
E-commerce business grows over time and has changed retail business behavior all over the world. To expand, e-commerce uses ads personalization to study customer needs and track customer behavior. This study aims to analyze the effect of perceived ads personalization towards online impulse buying tendency. The research model hypothesized the effect of perceived ads personalization towards online impulse buying tendency. The mediating variables in this study are perceived novelty, privacy concerns, advertising value, perceived relevance, creepiness, affective reactance, and attitudes towards ads. The study also used a moderating variable of purchasing frequency to distinguish how effective personalized advertising is in groups that are classified as high and the low-frequency buyer on e-commerce. This study using quantitative research methods with PLS-SEM data analysis. Respondents were taken by purposive sampling on millennial social media users in Jabodetabek. The results showed that perceived advertising personalization had a positive effect on perceived novelty, privacy concern, advertising value, perceived relevance, and creepiness. Furthermore, this study found perceived novelty, advertising value, and perceived relevance have a positive effect on attitudes towards ads. Creepiness indicates a positive effect on affective reactance, while privacy concern and affective reactance have a negative effect on attitudes towards ads. One of the findings is that attitudes towards ads had a positive impact on online impulsive buying tendency. The frequency of purchase is proven to be a moderator that weakens the influence of attitudes towards ads to online impulse buying tendency.Keywords: perceived ads personalization, perceived novelty, privacy concern, advertising value, perceived relevance, creepiness, affective reactance, attitudes toward ads, online impulse buying tendency, e-commerce